Case report of the brachial artery trifurcation: An anatomical study and concise literature review - Edward Clarke; Agata Olszewska; Michał Zarzecki; Wojciech Przybycień; Andrzej Dubrowski; Paweł Depukat; Karolina Barszcz; Andrzej Żytkowski (Elsevier, 2022)
Background: In most cases, the brachial artery ends in the cubital fossa at the level of the radial neck, where it divides into two terminal branches, i.e., the radial and ulnar arteries. However, there are numerous brachial artery variants regarding its origin, branching pattern and termination mode. Nonetheless, trifurcation of the brachial artery is rarely reported in the medical literature. Methods: Present report describes the aforementioned variant in the brachial artery termination - including its embryological background, classification, and practical significance. Case description: The anatomical variation presented herein was discovered during a routine dissection of an isolated adult right upper limb, fixed in 10% formalin solution. The anatomical relationships of the brachial artery (4.76 mm in diameter) in the arm were typical. In the cubital fossa, 39 mm below the interepicondylar line of the humerus, a trifurcation of the brachial artery was observed. In this case, the brachial artery had three terminal branches, i.e., the radial artery (it arose from the anterior aspect of the brachial artery end point and was 2.35 mm in diameter), the ulnar artery (that arose from the postero-medial aspect of the brachial artery end point and was 3.57 mm in diameter), and the radial recurrent artery (it arose from the lateral aspect of the brachial artery end point and was 1.84 mm in diameter). Conclusions: Different variants of the brachial artery termination may be observed. Trifurcation of the brachial artery may appear when an additional branch arises at the point of the artery's division into terminal branches. A varied origin and course of the radial artery might hinder the success of the vascular procedures associated with it.